Gypsum endolithic phototrophs under moderate climate (Southern Sicily): their diversity and pigment composition - Němečková, Kateřina; Mareš, Jan; Procházková, Lenka; Culka, Adam; Košek, Filip; Wierzchos, Jacek; Nedbalová, Linda; Dudák, Jan; Tymlová, Veronika; Žemlička, Jan; Kust, Andreja; Zima, Jan; et al. (Frontiers in Microbiology, 2023)
In this study, we used microscopic, spectroscopic, and molecular analysis to characterize endolithic colonization in gypsum (selenites and white crystalline gypsum) from several sites in Sicily. Our results showed that the dominant microorganisms in these environments are cyanobacteria, including: Chroococcidiopsis sp., Gloeocapsopsis pleurocapsoides, Gloeocapsa compacta, and Nostoc sp., as well as orange pigmented green microalgae from the Stephanospherinia clade. Single cell and filament sequencing coupled with 16S rRNA amplicon metagenomic profiling provided new insights into the phylogenetic and taxonomic diversity of the endolithic cyanobacteria. These organisms form differently pigmented zones within the gypsum. Our metagenomic profiling also showed differences in the taxonomic composition of endoliths in different gypsum varieties. Raman spectroscopy revealed that carotenoids were the most common pigments present in the samples. Other pigments such as gloeocapsin and scytonemin were also detected in the near-surface areas, suggesting that they play a significant role in the biology of endoliths in this environment. These pigments can be used as biomarkers for basic taxonomic identification, especially in case of cyanobacteria. The findings of this study provide new insights into the diversity and distribution of phototrophic microorganisms and their pigments in gypsum in Southern Sicily. Furthemore, this study highlights the complex nature of endolithic ecosystems and the effects of gypsum varieties on these communities, providing additional information on the general bioreceptivity of these environments.